ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA PERUSAHAAN CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA - Tudje, Susanti; Saerang, David; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The field of finance is a very important in a company, both in small and large-scale companies,or profitable motive and non-profit. The more advaced a company then the competition among companies getting tighter, thus making the company’s operation stabilized is  the most important to improve the ability to complete                                                                                                                                                                                                                                                                                                                                               and also to survive. The purpose of this research is to know and assess financial perfomances based on cash flow statement analysis on Consumer Goods Industry companies in BEI during 2012-2015.This type of research is a descriptive study using quatitative method and using the cash flow ratio analysis method, the ratio used in this study is the operating cash flow ratio, the ratio of cash flow to interest, the ratio of capital expenditure, the ratio of total debt, and the ratio cash flow to net income. From the result obtained by using ratio analysis method is less than 1,which can be conculeded that the financial performances of  Consumer Goods Industry lapse year 2012-2015 has a poor financial perfomances because the calculation result with the ratio of total debt 0,2. 0,12.0,07. and 0,13 which menas the company has not been able to pay all liabilities from cash flow derived from the normal activities of the company.Keywords : Cash Flow Statement, Operating Cash Flow, Cash Flow Ratios, Financial Perfomances